Family Purchasing Roles in Two Countries - Green, Robert T.; Cunningham, Isabella C. M. (Journal of International Business Studies, 1980)
This paper examines family decision-making roles among samples of consumers from the United States and Venezuela. The findings suggest considerable differences between the manner in which family purchasing decisions are made in the two countries for a wide variety of products and services. In general, the results indicate the dominance of the husband within the Venezuelan sample, whereas the U.S. sample is characterized by more joint husband/wife decisions.